1990
DOI: 10.1093/ije/19.4.1072
|View full text |Cite
|
Sign up to set email alerts
|

Measles Outbreaks in the Mozambican Refugee Camps in Malawi: The Continued Need for an Effective Vaccine

Abstract: Between November 1988 and January 1989, measles outbreaks occurred in 11 Mozambican refugee camps in Malawi with five camps principally affected. A total of 1214 cases were reported. Despite the reduction of the age of measles vaccination to six months in 1987, attack rates were highest in children aged 6-9 months (10-26%); rates were also high in the 0-5 month age group (3-21%). The case-fatality rate was high among children less than five years old (15-21%). Children were being inappropriately vaccinated, ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Clinical diagnosis of measles from a number of conditions that present with fever and rash symptoms [7] is difficult without laboratory confirmation, mostly for dark-skinned people. Therefore, laboratory testing should be an essential component of surveillance to confirm measles infection in order to establish the appropriate intervention, including vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical diagnosis of measles from a number of conditions that present with fever and rash symptoms [7] is difficult without laboratory confirmation, mostly for dark-skinned people. Therefore, laboratory testing should be an essential component of surveillance to confirm measles infection in order to establish the appropriate intervention, including vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) recognizes refugees as one of the high-risk groups for measles outbreaks. Several outbreaks have been reported among refugees and other emergency settings [7-9] due to their characteristic massive population displacements, overcrowding, high population densities and low vaccination coverage [10,11]. Overcrowding is associated with the transmission of higher infectious doses of measles virus, resulting in more severe cases of clinical disease [12], which makes measles more often the leading cause of mortality among children in refugee populations.…”
Section: Introductionmentioning
confidence: 99%
“…Measles case-fatality ratios in children in complex emergencies have been as high as 20-30%. 18,19 During a famine in Ethiopia, measles alone or in combination with wasting accounted for 22% of 159 deaths of children under 5 years, and 17% of 72 deaths of children aged 5-14 years. 20 Progress in global control has reduced the likelihood of measles outbreaks in some regions, although outbreaks can occur in refugee and internally displaced populations with low levels of immunity or vaccination coverage.…”
Section: Measlesmentioning
confidence: 99%
“…In Malawi, measles vaccine is given after 9 months of age as in other developing countries. It has been reported that measles VE was 95 % at 9 months in Niger [4], and more than 90 % in Mozambican refugee camps in Malawi [5]. However, measles accounted for 10n4% of hospital admissions (the fourth cause), and 8n7% of in-patient mortality (the fifth cause) in children under 5 years in 1992 [6].…”
Section: Introductionmentioning
confidence: 99%